MENCEGAH DAN MENANGANI STIGMA SOSIAL TERKAIT COVID 19 (SUATU PENDEKATAN STUDI LITERATURE REVIEW) - Rahman, Irpan Ali (HEARTY, 2022)
The COVID-19 virus was first discovered in late December 2019 in Wuhan, China, the number of people infected with the coronavirus is increasing rapidly all over the world, and public and anxiety levels are increasing in many areas. During the COVID-19 outbreak, a wave of fear and phenomena in society emerged. So that stigma arises which is a negative label attached to someone given by society. Efforts to change community stigma are by designing effective anti-stigma programs to break down misperceptions about COVID-19, increase public knowledge about COVID-19, and spread positive messages and support. The research method is a literature review study and includes qualitative data sources from a study. The search strategy for relevant Indonesian and English articles, Literature searches are carried out through online searches on Google Scholar and also the SINTA website (Science and Technology Index). There are 15 articles that are grouped into several stigma topics related to COVID-19. 4 articles discuss the incidence of stigma, 7 articles discuss the psychological impact of stigma related to COVID-19, and 4 articles discuss social stigma related to COVID-19. Conclusion To fight stigmatization related to COVID-19 is to Spread the facts, Engage social influencers, and Amplify the voices of people who are recovering from COVID-19.